Can Instagram be used to deliver an evidence-based exercise program for young women? A process evaluation - Rachel G. Curtis; Jillian C. Ryan; Sarah M. Edney; Carol A. Maher (BMC, 2020)
Abstract Background Instagram provides an opportunity to deliver low cost, accessible and appealing physical activity content. This study evaluated the feasibility of delivering an exercise program for young women using Instagram. Methods A single-group pre- and post-intervention trial examined the feasibility and preliminary efficacy of a 12-week Instagram-delivered program with young inactive women (n = 16; M = 23 years), which prescribed running and body weight exercises to complete three times per week. Daily Instagram posts delivered the exercises, video demonstrations and motivational content. Feasibility was evaluated by examining exposure (Instagram posts viewed per week), engagement (likes, comments and tags on Instagram posts; number of exercise sessions completed per week; retention, defined as completion of the online survey at weeks 6 and 12), and acceptability [whether the program increased participants' motivation to exercise (1 = strongly disagree-5 = strongly agree); satisfaction with the program (1 = not satisfied-5 = very satisfied)]. Preliminary efficacy was evaluated by comparing baseline and 12-week self-reported physical activity (IPAQ short-form) and fitness (cardiorespiratory and muscle strength; 1 = very poor-5 = very good, International Fitness Scale) using the Exact sign test. Results On average, participants reported seeing six posts in their Instagram feed per week. Posts received an average of five likes (IQR = 3-6). A total of four comments and one tag were observed across all posts. On average, participants reported completing two exercise sessions per week. Retention was 88% at 6 weeks but dropped to 56% at 12 weeks. Participants reported increased motivation to exercise (Mdn = 4, IQR = 3-4) and were satisfied with the program (Mdn = 4, IQR = 3-4). Only self-reported cardiorespiratory fitness showed a meaningful, though nonsignificant, improvement (MdnΔ = 1, IQR = 0-1, p = .06). Conclusions Although Instagram has the potential to deliver a low cost, convenient exercise program for young women, additional research is needed to identify methods of improving engagement (interaction with the Instagram content, exercise sessions completed, and retention in the program). Future research could examine the use of behaviour change theory and provide information that enables participants to tailor the exercises to their interests and needs. Additionally, the use of objective assessments of physical activity and fitness among a larger participants sample is needed.